Sprawozdanie piłkarskie – u źródeł gatunku - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article characterizes the football match reports published in Sports Review in 1921. An analysis of the material collected reveals a number of characteristics in the interwar text, i.e., limited imagery, concreteness/discursive juxtaposition, the use of the present tense in describing the game, open (sometimes expressive) evaluation of the individual players’ performance and the teams’ abilities, as well as a missionary style of reporting, in which the journalist takes up universal issues regarding football, sports and physical culture. The analysis outlines the differences between old-time and contemporary realizations of the genre.